'An Empire O'er the Disentangled Doom': Captivity and the re-staging of Prometheus in the twenty-first century. (February 2016) - Smith, Stephanie A.
Abstract : Origin remains a powerful trope in sf, particularly if Shelley's Frankenstein is seen as foundational because it is about origins, as evidenced by the creature's search for a place in a world from which he is abjected. Yet, it is precisely this terrible abjection that makes the creature so compelling. The myth of Prometheus, upon which Frankenstein relies, continues to haunt Western culture: witness two technologically enhanced retellings – the film Prometheus and the UK stage play of Frankenstein . This essay explores these new versions to argue that the changes in perspective and narrative show how misogynist fears about technology, sex/ death and reproduction still undergird cultural production in the twenty-first century.